Relation between Parental Education and Children’s Healthful Lifestyle: Parents’ Education and children’s Lifestyle - Zeinali, Farahnaz; Peiravian, Farzad; Yousefi, Nazila (Iranian Journal of Pharmaceutical Sciences, 2019)
Because of the important role of parents’ socioeconomic condition in their children’s health, the present paper aimed to evaluate the relationship between the parents’ education and children’s healthful lifestyle, including breastfeeding, nutrition, supplement intake, smoking, and personal hygiene. Parents’ behavior is an important factor that affects children’s health status. Accordingly, a cross-sectional descriptive analysis was conducted using a self-administrated anonymous questionnaire. A total of 600 anonymous questionnaires were distributed among the children’s parents in primary schools in Tehran, Iran, of which 62% were returned. Responses showed that 89.2% of mothers intended to breastfeed and 69% of children had suitable nutrition. Additionally, the study result indicated a significant correlation between parents’ education and children’s personal hygiene. There was a significant relation between parents’ education and parents’ smoking as well. Furthermore, there was a significant relation between mothers’ education and supplement intake in their children. Therefore, parents’ education and health literacy are the main factors in children’s health that should be addressed by policymakers.